Sosialisasi Budidaya Kurma dan Konsep Green Constitution - Hayatul Ismi; Yeni Kusumawaty; Evi Deliana; Ulfia Hasanah; Dessy Artina; Erdiansyah Erdiansyah; Fenny Trisnawati (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
Rokan Hulu Regency is famous for its religious tourism with the construction of Madani Islamic Center Mosque which is visited by thousands of visitors from different regions every week. To support the characteristic of this religious tourism area, it was planned to cultivate the date palms which was inspired by the Holy Qur'an to increase the income and welfare of the community of Babussalam Village. In relation to the introduction of relatively new date fruit cultivation in Indonesia, socialization and counseling on the potential of date palms and village rules concepts in line with green constitution were necessary. This counseling aimed to provide guidance to the community of Babussalam Village Rokan Hulu District Rokan Hulu as a village that has a program of cultivation of date palms through village regulations and to improve the living standards of villagers in Babussalam as well as a pilot village of dates cultivation. Based on the five indicators (increase of participant's knowledge, the activity of the participants, the suitability of the training materials to the needs of the participants, the impact of future activity implementation and the participation rate based on the number of participants), the activity is considered successful and can improve knowledge, motivation and of community and the apparatus of Babussalam village in implementing date palm cultivation as a trade mark for Rokan Hulu Regency as a religious tourism destination in the future.